Optimization of dialysate bicarbonate in patients treated with online haemodiafiltration - Montagud-Marrahi, Enrique (Clin Kidney J, 2020)
BACKGROUND: Metabolic acidosis is a common problem in haemodialysis patients, but acidosis overcorrection has been associated with higher mortality. There is no clear definition of the optimal serum bicarbonate target or dialysate bicarbonate. This study analysed the impact of reducing dialysate bicarbonate from 35 to 32 mEq/L on plasma bicarbonate levels in a cohort of patients treated with online haemodiafiltration (OL-HDF). METHODS: We performed a prospective cohort study with patients in a stable chronic OL-HDF programme for at least 12 months in the Hospital Clinic of Barcelona. We analysed pre- and post-dialysis total carbon dioxide(TCO(2)) before and after dialysate bicarbonate reduction from 35 to 32 mEq/L, as well as the number of patients with a pre- and post-dialysis TCO(2) within 19–25 and ≤29 mEq/L, respectively, after the bicarbonate modification. Changes in serum sodium, potassium, calcium, phosphorous and parathyroid hormone (PTH) were also assessed. RESULTS: We included 84 patients with a 6-month follow-up. At 6 months, pre- and post-dialysis TCO(2) significantly decreased (26.78 ± 1.26 at baseline to 23.69 ± 1.92 mEq/L and 31.91 ± 0.91 to 27.58 ± 1.36 mEq/L, respectively). The number of patients with a pre-dialysis TCO(2) >25 mEq/L was significantly reduced from 80 (90.5%) to 17 (20.2%) and for post-dialysis TCO(2)  >29 mEq/L this number was reduced from 83 (98.8%) to 9 (10.7%). PTH significantly decreased from 226.09 (range 172–296) to 182.50 (125–239)  pg/mL at 6 months (P < 0.05) and post-dialysis potassium decreased from 3.16 ± 0.30 to 2.95 ± 0.48 mEq/L at 6 months (P < 0.05). Sodium, pre-dialysis potassium, calcium and phosphorous did not change significantly. CONCLUSIONS: Reducing dialysate bicarbonate concentration by 3 mEq/L significantly and safely decreased pre- and post-dialysis TCO(2), avoiding acidosis overcorrection and improving secondary hyperparathyroidism control. An individualized bicarbonate prescription (a key factor in the adequate control of acidosis) according to pre-dialysis TCO(2) is suggested based on these results.